“Implementación de un sistema automatizado de lavado de jabas para incrementar la productividad en sección lavado, empresa Servijabas S.A.C, 2018” - Olivera Sagastegui, Hiorka Tatiana (2019)
ABSTRACT This research was realized by the aim to determine if the implementation of an automated system of wash of crates allows to increase the productivity in the section of wash of the company Servijabas S.A.C, 2018. The research is quantitative, of pre experimental design. 350 samples were taken as a sample of crates from the washing section of the company Servijabas S.A.C company; a valid and reliable observation guide was developed where the mechanical and manual cleaning processes of the washing section of Servijabas S.A.C. The results are presented by tables. There was obtained as result that with the implementation of an automated system of wash of crates increases significantly the productivity in the section of wash of the company Servijabas S.A.C, depending on which the productivity increases in 124 % in 4 of 5 phases of the process of wash, the same one that man / machine has been calculated depending on 4 hours. This allows to affirm then that a system of automated wash will allow a major productivity with a minor number of workers. The implementation of an automated system in the process of washing of crates in the company Servijabas S.A.C represents an opportunity to increase productivity, thus contributing to the growth and development of the company. Said implementation is carried out in four of the five phases of the washing in a single machine and in the shortest time; this has to do with greater market demand, in turn, to integrate new production technologies and increase the quality of the washing of the crates.